Toxicological Characterization of Six Plants of the Beninese Pharmacopoeia Used in the Treatment of Salmonellosis. (1st July 2019) - Legba, Boris; Dougnon, Victorien; Deguenon, Esther; Agbankpe, Jerrold; Senou, Maximin; Aniambossou, Alidah; Gbaguidi, Carène; Sintondji, Kevin; Baba-Moussa, Lamine; Dougnon, Jacques
Abstract : Recent studies reported interesting ethnopharmacological, antibacterial, and phytochemical data on some medicinal plants used in the traditional treatment of salmonellosis in Benin. Unfortunately, very little data exists on the toxicity of these species. This study aims to evaluate chemical characteristic of six Benin pharmacopoeial plants used in the traditional treatment of salmonellosis in Benin. The acute toxicity of aqueous and ethanolic extracts of Psidium guajava, Vernonia amygdalina, Cajanus cajan, Phyllanthus amarus, Uvaria chamae, and Lantana camara was evaluated according to OECD Guideline 423 at a single dose of 2000 mg/kg body weight on Wistar rats. Histological sections were performed on the liver and kidneys to confirm hematological and biochemical data. The content of aluminum, chromium, cadmium, copper, iron, lead, zinc, arsenic, selenium, and manganese was measured in 10 mg of each extract by the inductively coupled plasma optical emission spectroscopy (ICPOES) method. The results of our study generally show the absence of significant effect of the extracts on the hematological and biochemical parameters of the rats. However, with the exception of the aqueous and ethanolic extracts of Psidium guajava root and the ethanolic extract of Phyllanthus amarus (P>0.05), all the extracts have a significant effect on the aspartate aminotransferase (ASAT) level, with a variable threshold of significance (0.0001< P ≤ 0.05). No mortalities and no renal histological conditions were recorded in the treated rats. In general, the heavy metal contents of the extracts do not exceed the standards set by the WHO/FDA except for a few extracts. Arsenic was not detected in any extract, while aluminum and chromium were detected at levels above the WHO/FDA standards. On the basis of these data, it appears that the six plants studied do not show any toxicity. In view of the pharmacological and chemical data previously available, these plants are good candidates for the development of improved traditional medicines with antibacterial and particularly anti- Salmonella properties.